2019
DOI: 10.1186/s13018-019-1355-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Modic type 2 change have a severe radiographic representation in the process of lumbar degeneration: a retrospective imaging study

Abstract: Background There are few studies to investigate changes in imaging parameters of Modic changes (MCs). The imaging studies examining the distinctions in the lumbar sagittal parameters between MCs and lumbar disc degeneration (LDD) are still lacking. The purpose of this study was to identify the differences in the lumbar sagittal parameters among patients for LDD with/without Modic type 2 change (MII). Methods A total of 208 patients with lumbar degenerative disease from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(35 reference statements)
0
10
1
Order By: Relevance
“…Also, type 1 Modic change, which is widely observed in early IVD degeneration, is thought to be an autoimmune response with CEP damage [54]. Indeed, these image manifestations are strong evidence for IVD degeneration prognostication and early management [55][56][57]. Additionally, studies have found that inflammatory factors are upregulated in serum from IVD herniation patients.…”
Section: Implications For Clinical Management Of Ivd Degenerationmentioning
confidence: 99%
“…Also, type 1 Modic change, which is widely observed in early IVD degeneration, is thought to be an autoimmune response with CEP damage [54]. Indeed, these image manifestations are strong evidence for IVD degeneration prognostication and early management [55][56][57]. Additionally, studies have found that inflammatory factors are upregulated in serum from IVD herniation patients.…”
Section: Implications For Clinical Management Of Ivd Degenerationmentioning
confidence: 99%
“…[ 13 , 14 ] in 1988. It, coupled with their more severe radiographic performance than simple disc degeneration [ 15 , 16 ] and positive correlation with CLBP [ 17 ], has also been attracted widespread academic attention. Although a recent paper from the Wakahama Spine Study [ 17 ], have reported a positive association between MCs and LBP, the most recent systematic review on this topic [ 18 ] concludes that the associations between MCs and LBP-related outcomes are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Although the etiology of MC is still unclear, 4 microfracture of the endplate is thought to be a key link in MC formation. 5 As the cartilage endplate of the vertebral body changes, the herniated disc associated with degenerative disc disease will also change. 2 Among the different MC types, MC I is often considered to have a high correlation with clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%